HUBUNGAN MUTU PELAYANAN KESEHATAN DENGAN TINGKAT KEPUASAN PASIEN BPJS DI RAWAT INAP - Mirnawati, Mirnawati; Fitriyah, Erna Tsalatsatul; Roni, Faishol (Jurnal EDUNursing, 2021)
Abstract Quality is the most important thing for the service company holder. It refers to action that should be well like the safe guaranty for patient. In the implementation of public service, still a lot of missing things that affect to the public service quality. The low costumer satisfication will influencing the health facility provitabilities. In other hand, the employ behavior will also affect to the patient satisfication, wherease the patient needs is always increase everytime, and it also happen to the demand of service quality which given. This research aim is knowing the association service quality with the satisfication of BPJS inpatient. This article using literature review method which use google scolar as the support database that suitable with inclusion and exclusion criteria. Based on the ten identified journals, those are showing that the association is exist between the service qualities with the satisfication of BPJS inpatient. There is an association between the service qualities with the satisfication of BPJS inpatient.Keyword: service quality, demand level, BPJS Inpatient